2020
DOI: 10.1111/jog.14301
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thiol disulfide balance in early‐stage endometrial cancer

Abstract: Aim: We carried out this research to assess thiol disulfide balance in patients with early-stage endometrial cancer. Methods: Fifty-seven endometrial cancer patients and 60 age-matched healthy subjects volunteered for this study. Thiol disulfide parameters and the ratios of these parameters were examined using a colorimetric system. We also evaluated total antioxidant capacity, total oxidant capacity and oxidative stress index. Results: Subjects with endometrial cancer had statistically significantly lower ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 34 publications
(71 reference statements)
5
15
0
Order By: Relevance
“…In the study of endometrial cancer, it was stated that the ratios of oxidants and antioxidants may be useful in demonstrating oxidative stress. 8 The ratio of oxidants to antioxidants (disulfide/native thiol ratio) was increased in patients with breast and endometrial cancers similar to patients in our study. We may conclude that dynamic TD homeostasis is in the direction of oxidation in patients with cervical cancer as in patients with endometrial and breast cancers.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In the study of endometrial cancer, it was stated that the ratios of oxidants and antioxidants may be useful in demonstrating oxidative stress. 8 The ratio of oxidants to antioxidants (disulfide/native thiol ratio) was increased in patients with breast and endometrial cancers similar to patients in our study. We may conclude that dynamic TD homeostasis is in the direction of oxidation in patients with cervical cancer as in patients with endometrial and breast cancers.…”
Section: Discussionsupporting
confidence: 86%
“…In the study of endometrial cancer, it was reported by Sezgin et al that as the rate of disulfide/native thiol increased, the depth of myometrial invasion also increased. 8 Our study showed that the levels of disulfide were found to be progressively increased as the stage of the cervical cancer progressed. The evolving of this oxidative environment is probably due to the effect of HPV E6/7 oncoproteins to increase reactive oxygen species in cellular metabolism.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations